Intuitionistic anti fuzzy normal subrings over normed rings - Nour Abed Alhaleem,; Abd Ghafur Ahmad, (Penerbit Universiti Kebangsaan Malaysia, 2022)
In this paper, we initiate the notion of intuitionistic anti fuzzy normed normal subrings and generalize various related properties. We extend the notion of intuitionistic fuzzy normed subrings to intuitionistic anti fuzzy normed normal subrings. Further, we study the algebraic nature of direct product of intuitionistic anti fuzzy normed normal subrings and establish and examine some imperative properties of such products. We also provide some essential operations specially subset, complement and intersection relating to direct product of intuitionistic anti fuzzy normed normal subrings. Then, we generalize the relation between the intuitionistic characteristic function and direct product of intuitionistic anti fuzzy normed normal subrings.